2003
DOI: 10.1021/np030323j
|View full text |Cite
|
Sign up to set email alerts
|

A New Phloroglucinol Derivative from the Brown Alga Eisenia bicyclis:  Potential for the Effective Treatment of Diabetic Complications

Abstract: A new phloroglucinol derivative (1) and two known compounds (2 and 3) were isolated from the brown alga Eisenia bicyclis. These isolates exhibit inhibitory activity on glycation and alpha-amylase. Their structures were determined on the basis of spectroscopic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
103
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 7 publications
5
103
1
3
Order By: Relevance
“…These algae are known to contain several phlorotannins, viz., eckol, 1) dieckol, 1) 6,6 0 -bieckol, 2) 8,8 0 -bieckol, 2) and phlorofucofuroeckol-A (PFF-A). 3) Phlorotannins have been reported to have certain biological activities, such as antioxidation, 4) bactericide, 5) anti-cancer, 6) anti-diabetic complications, 7,8) and chemoprevention against several vascular diseases. 9,10) Although some anti-inflammatory activities of phlorotannins have also been reported, 11,12) their inhibitory effect on histamine release from the stimulated cultured cells is still unknown.…”
mentioning
confidence: 99%
“…These algae are known to contain several phlorotannins, viz., eckol, 1) dieckol, 1) 6,6 0 -bieckol, 2) 8,8 0 -bieckol, 2) and phlorofucofuroeckol-A (PFF-A). 3) Phlorotannins have been reported to have certain biological activities, such as antioxidation, 4) bactericide, 5) anti-cancer, 6) anti-diabetic complications, 7,8) and chemoprevention against several vascular diseases. 9,10) Although some anti-inflammatory activities of phlorotannins have also been reported, 11,12) their inhibitory effect on histamine release from the stimulated cultured cells is still unknown.…”
mentioning
confidence: 99%
“…Furthermore EBE has been known to have anti-oxidant effects and antiinflammatory effects (Okada et al, 2004;Whitaker and Carlson, 1975 As shown in Fig. 1A and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The plates were then agitated on a shaker (120 rpm) for 10 min at room temperature. A 200 µL aliquot of reaction solution (7.5 mL of 0.5 M Tris HCl buffer, pH 7.4; 100 mg of albumin from human serum; 1 mL of 1.5% Tween 20 solution; 0.1 mL of 7.5 mM FAD; 1 mL of 150 mM glucose 6-phosphate; 90 µL of 50 mM NADP; 300 U of yeast glucose 6-phosphate dehydrogenase; 45 mg of MTT; 150 µL of 50 Nakamura et al, 1996;Okada et al, 2004;Jung et al, 2010;Yoon et al, 2011). In particular, phlorotannins, the major metabolites of Eisenia and Ecklonia species, are polyphenolic compounds that have a variety of positive physiological effects such as antioxidation, antidementia, antihyperlipidemic, and angiotensin-converting enzyme I and tyrosinase inhibitory activities (Kang et al, 2004;Jung et al, 2006Jung et al, , 2010Yoon et al, 2008Yoon et al, , 2009.…”
Section: Qr Induction Assaymentioning
confidence: 99%